RUJUKAN BERJENJANG DALAM PELAYANAN RUMAH SAKIT DITINJAU DARI SEGI HUKUM - Novi Hamzah (Jurnal HUKUM BISNIS, 2020)
To protect all citizens, the National Social Security System Law No 40 of 2004 is included in the National Health Insurance social health insurance membership. Then Act Number 24 of 2011 concerning the Social Security Organizing Body hereinafter abbreviated as BPJS which is followed up with Presidential Regulation Number 12 of 2013 concerning Health Insurance as amended by Presidential Regulation Number 111 of 2013 concerning Amendment to Presidential Regulation Number 12 of 2013 concerning Guarantees Health. Also the Health Service Referral system Regulation of the Minister of Health of the Republic of Indonesia Number 1 of 2012 has been set. It is expected that with these regulations in addition to increased health access satisfaction from patients will also increase. One of the problems in implementing a referral system is that there are limited resources and infrastructure which are very important in health institutions to provide minimal health services. The implementation of this system will not run well if the implementation is not in accordance with the provisions of the policy or guidelines Keywords: National Health Insurance, Tiered Referral, Health services